Characterization of secondary metabolites from hexane and chloroform crude of four Trametes spp. isolated from Sarawak using analysis of GS-MS - Ali, Afni; Muid, Sepiah; Yusuf, Umi Kalsom (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
The secondary metabolite from hexane and chloroform crude extract of fruiting body and culture mycelia of Trametes cervina, T. ljubarski, T. velutina and T. orientalis were investigated and characterized using gas chromatography-mass spectrometry (GC-MS). Forty peaks of compounds from a series of volatile hydrocarbons and hydrocarbon derivatives were detected on the GC-MS chromatogram of each isolates and about 30 compounds were identified based on the library database. In the hexane crude, 17 compounds were identified for T. cervina, 14 compounds for T. ljubarski, 13 compounds for T. velutina and 21 compounds for T. orientalis, while in the chloroform crude extract 12 compounds were identified for T. cervina, 17 compounds for T. ljubarski, 15 compounds from T. velutina and 12 compounds for T. orientalis. The most common compound detected in the extract of the Trametes spp. were cyclohexane, heptane, octane, nonane, decane, undecane, 1-Butenyl methyl ketone, 1-Ethyl-4-methylcyclohexane, 2-Hexyl-1-octanol, 3-Hydroxy-3-methylvaleric acid, 2-Chlorocyclohexanol, n-Nonadecanol, tetratetracontane, hexatriacontane. tetrapentacontane and hexatriacontane respectively based on the library database. Tetrapentacontane (TCC1) and hexatriacontane (TCC2) which represented 48.01% and 19.61% of the total area was the major compound in chloroform extract of T. cervina, whereas tetracontane (TLC1) which represented 34.48% of the total area and diethylene glycol dibenzoate (TVC1) represented 13.13% of the total area was the major compound in chloroform extract of T. ljubarski and T. velutina respectively. Among the identified compounds, hexatriacontane which identified from T. cervina, T. ljubarski, and T. velutina and hexadecanoic acid from T. orientalis, were previously reported to have antimicrobial activity. Thus the metabolite profiling of the Trametes spp. not only potential to be used for their identification but also allowed the exploration of potential biological active compound from the species.